Musicianship-Related Structural and Functional Cortical Features Are Preserved in Elderly Musicians - Rus-Oswald, Oana G.; Benner, Jan; Reinhardt, Julia; Bürki, Céline; Christiner, Markus; Hofmann, Elke; Schneider, Peter; Stippich, Christoph; Kressig, Reto W.; Blatow, Maria (Frontiers in Aging Neuroscience, 2022)
Background: Professional musicians are a model population to explore basic auditory function, sensorimotor and multisensory integration, as well as training-induced neuroplasticity. The musician brain exhibits distinct structural and functional cortical features, however, little is known about how these features evolve during aging. This multiparametric study aimed to examine the functional and structural neural correlates of lifelong musical practice in elderly professional musicians. Methods: 16 young musicians, 16 elderly musicians (age >70) and 15 elderly non-musicians participated in the study. We assessed gray matter metrics on a whole-brain and ROI level using high-resolution MRI with Freesurfer automatic segmentation and reconstruction pipeline. We used Brainvoyager semi-automated segmentation to explore individual auditory cortex morphotypes. Further, we evaluated functional BOLD activations in auditory and non-auditory regions using fMRI with an attentive tone listening task. Finally, we performed discriminant function analyses based on structural and functional ROIs. Results: A general reduction of gray matter metrics distinguished elderly from young subjects on a whole-brain level, corresponding to widespread natural brain atrophy. Age- and musicianship dependent structural correlations revealed group specific differences in several clusters including superior, middle and inferior frontal as well as perirolandic areas. In addition, elderly musicians exhibited increased gyrification of auditory cortex, similar to young musicians. During fMRI elderly non-musicians activated predominantly auditory regions, whereas elderly musicians co-activated a much broader network of auditory association areas, primary and secondary motor areas as well as prefrontal and parietal regions, similar to albeit weaker than in young musicians. Also, group specific age- and musicianship dependent functional correlations were observed in frontal and parietal regions. Moreover, discriminant function analysis could separate the groups with high accuracy based on a set of specific structural and functional, mainly temporal and occipital ROIs. Conclusion: In conclusion, despite naturally occurring senescence, elderly musicians maintained musicianship-specific structural and functional cortical features. The anterior and posterior brain regions, which showed both structural as well as functional differences to non-musicians might be of relevance for the aging musicians’ brain. To what extent lifelong musical activity may have a neuroprotective impact needs to be further addressed in larger longitudinal studies.